Dynamic stability metrics exhibit different periods of familiarization to treadmill walking - Tarique Siragy; Allen Hill; Julie Nantel (Scientific Reports)
Abstract The dynamic nature of gait heightens the risk of falling. Treadmill-based protocols are used to assess dynamic stability as they allow for uninterrupted gait. However, walking on treadmills differs from overground and individuals require time to adapt to the treadmill before reaching a steady-state gait. While familiarization was examined for gait kinematics, it remains uninvestigated for dynamic stability. As dynamic stability metrics quantify aspects of neuromuscular control, altered sensorimotor input from the treadmill would require familiarization to avoid confounding factors in the interpretation of fall risk. Dynamic stability metrics were assessed for twenty healthy young adults (18-30yrs) during two 10-min sessions of treadmill walking separated by one week. No familiarization in the mediolateral direction occurred but fluctuations in the anteroposterior direction for the Harmonic Ratio (session 1) and Margin of Stability (session 2) occurred. Fluctuations may reflect different strategies used to adjust to the treadmill. Specifically, participants altered step length and upper body posture in session 1 and 2, respectively. This may indicate that more than ten minutes are necessary for dynamic stability metrics to reach a steady-state. Further, treadmill exposure may modulate the motor strategies used to adjust dynamic stability during familiarization periods.